2019
DOI: 10.3126/nmcj.v21i3.26441
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Hyperbaric Oxygen Exposure on Bacterial Toxin Antigen and Collagen Induced Arthritis in Animal Model

Abstract: Anti-cyclic citrullinated peptide antibody (ACPA) is a specific autoantibody that binds with citrullineamino acid in rheumatoid arthritis (RA). Interleukin-17a (IL-17a) is one of the cytokines that play an important role in chronic inflammation during the process of autoimmune diseases. Bacterial toxin antigen and collagen induced arthritis (ACIA) is the gold standard of RA animal model. The aim of this study was to see the effect of hyperbaric oxygen (HBO) exposure on ACIA animal models. ACIA model was made b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…It has been implicated in the development of Parkinson's disease and enrolled in the induction of apoptosis and regulation of the cellular response to hypoxia stress 42 . Harnanik et al showed that SIAH1 and SIAH2 help the differentiation of Treg cells into Th17 by increasing the activity of the IL‐17a promoter in the T‐cell and increases RA progression in bacterial toxin antigen and collagen‐induced arthritis (ACIA) models 43 . The role of SIAH1 in TB infection and RA is not clear, and more research is needed.…”
Section: Gene Signatures and Pathways Shared Between Tb And Ramentioning
confidence: 99%
“…It has been implicated in the development of Parkinson's disease and enrolled in the induction of apoptosis and regulation of the cellular response to hypoxia stress 42 . Harnanik et al showed that SIAH1 and SIAH2 help the differentiation of Treg cells into Th17 by increasing the activity of the IL‐17a promoter in the T‐cell and increases RA progression in bacterial toxin antigen and collagen‐induced arthritis (ACIA) models 43 . The role of SIAH1 in TB infection and RA is not clear, and more research is needed.…”
Section: Gene Signatures and Pathways Shared Between Tb And Ramentioning
confidence: 99%